Governed by numbers: Financing as a form of government of the university in Chile - Vicente Sisto; Pontificia Universidad Católica de Valparaíso; Centro de Investigación para una Educación Inclusiva (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2017)
In the context of the new models of public management, this article studies financing mechanisms linked to standards and indicators as forms of government at a distance. The case of the Chilean university system is considered by means of two studies. The first analyzes the official discourse contained in 52 documents issued between 2010 and 2015 by national and sectorial authorities, addressing arguments and rhetorical constructions that support the implementation of these mechanisms. The University as an institution in debt to society emerges as the main discursive figure that justifies a financing conditioned by indicators, as a form of government. The second study descriptively analyzes 175 normative and procedural official documents issued between 2010 and 2015. A map emerges with the main indicators that, inserted in financing mechanisms, challenge the University, its actors and their daily work. These studies show that both the rhetoric that justifies as well as the instruments are part of an assembly that transforms the activity of the University and its actors into financeable, and therefore, governable objects, setting objectives and modeling their future.